Integrating eHealth data analytics into Continuing Professional Development for medical practitioners: an ecosystemic perspective - Pizzuti, Carol (Frontiers in Medicine, 2025)
This perspective explores the evolving landscape of Continuing Professional Development (CPD) for medical practitioners, focusing on the use of eHealth data analytics to strengthen CPD programs and practices. Traditional didactic approaches to CPD have demonstrated limitations, prompting a shift toward outcome-focused and workplace-based CPD activities. This trend aligns with medical regulations that emphasize integrating clinical performance and patient health data into professional learning for practice change and improved care. Leveraging eHealth data analytics for self-assessment, improved clinical performance, and effective CPD is emerging as an opportunity. Both academia and industry are actively working to link clinical performance data, continuous learning, and CPD to promote safer, higher-quality care. eHealth data analytics enables personalized CPD by addressing specific performance gaps and clinical needs, enhancing learning impact and health outcomes. However, current research highlights challenges such as data accessibility, availability, and quality, technological interoperability, and resistance to change—both organizationally and at the individual level. These obstacles underscore the need for a holistic approach, innovative thinking, and evidence-based solutions in the ever-changing fields of medical regulation and continuing education. Further research is essential to substantiate the value of eHealth data for CPD, build a comprehensive depiction of the CPD ecosystem, and guide successful implementation and cultural shifts. Building a data-driven CPD ecosystem requires interdisciplinary collaboration and a commitment to real-world solutions. Future efforts must focus on both theoretical and applied exploration to fully realize the value of eHealth data analytics, enabling personalized, impactful CPD in a fast-moving healthcare environment.